2015
DOI: 10.1111/ped.12655
|View full text |Cite
|
Sign up to set email alerts
|

Massive pericardial effusion due to intrapericardial mixed germ cell tumor in a premature baby

Abstract: Primary cardiac tumor is uncommon in childhood, with an incidence of 0.06-0.32%, and intrapericardial teratoma represents an exceptional rarity among these entities. Germ cell tumors (GCT) are rare, representing only 1-3% of childhood tumors. Twenty per cent of GCT are malignant and are associated with age and location. Extragonadal involvement accounts for nearly half of the cases. Anterior mediastinum is a common location of malignant germ cell tumors, yet pericardial and aortic adventitia involvement have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
(14 reference statements)
0
5
0
1
Order By: Relevance
“…Tumor rupture can cause pleural or pericardial effusion (14-16) and engage the pericardium. Malignant pericardial effusion is often sporadic and observed in children (8,9,15) and adults (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor rupture can cause pleural or pericardial effusion (14-16) and engage the pericardium. Malignant pericardial effusion is often sporadic and observed in children (8,9,15) and adults (15).…”
Section: Discussionmentioning
confidence: 99%
“…In cases with anterior mediastinal tumor, the clinical presentation is usually caused by compression on surrounding structures (7). A review of the literature showed that pericardial effusion can rarely be the first manifestation of EGGCT and only few case reports have shown tumoral involvement of pericardium (8)(9)(10)(11), which is more common in children and even premature infants (9).…”
Section: Introductionmentioning
confidence: 99%
“…There have been sporadic case reports of a variety of tumors involving the pericardium, most frequently teratomas. After teratomas, a multitude of tumors have been reported to cause pericardial effusions, including paraganglioma, leukemia, schwannoma, carcinoid tumor, primitive neuroectodermal tumor, rhabdoid tumor, pheochromocytoma, melanoma and extragonadal germ cell tumors [ 6 , 9 , 10 ]. It is important to that all of these, including nonseminomatous germ cell tumors, are extremely rare causes of pericardial effusion, with none of these having been shown to cause more than a handful of cases via literature review of case reports, retrospective analyses or meta-analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Extragonadal seminomatous tumors usually present with an elevated b-HCG and LDH whereas elevations in b-HCG and AFP are commonly seen with extragonadal nonseminomatous neoplasms. Although mediastinal germ cell tumors have been well described, invasion into the pericardium and resultant malignant pericardial effusion is a rare phenomenon which has been the topic of sporadic case reports involving mainly pediatric patients [ 6 , 7 ]. We present a rare care of intrapericardial EGGCT and presented concomitantly with malignant pericardial effusion.…”
Section: Introductionmentioning
confidence: 99%
“…4 Tedavide her hasta bireysel olarak değerlendirilmekle beraber, semptomatik olanlarda yüksek başarı oranlarıyla cerrahi rezeksiyon önerilmektedir. 7 Tedavi yönetimi gebeliğin gestasyonel evresine ve tümörün histolojisine bağlıdır. Eğer gebeliğin sonlandırılması düşünülüyorsa kitle natürü iyice değerlendirilmelidir.…”
unclassified